Will Remotely Based Pulmonary Rehabilitation Water Down Its Effectiveness? - Himanshu Rawal; Sharon D. Cornelison; Sheryl M. Flynn; Jill A. Ohar (Life, 2021)
Despite numerous benefits, traditional Pulmonary Rehabilitation (PR) as a resource remains underutilized in chronic lung disease. Less than 3% of eligible candidates for PR attend one or more sessions after hospitalization due to many barriers, including the ongoing COVID-19 pandemic. Emerging alternative models of PR delivery such as home-based PR, tele-rehabilitation, web-based PR, or hybrid models could help address these barriers. Numerous studies have tested the feasibility, safety, and efficacy of these methods, but there is wide variability across studies and methods. We conducted a literature review to help determine if these alternative delivery methods watered down the effectiveness of PR. To evaluate the effectiveness of remotely based PR, the authors performed a literature search for randomized controlled trials (RCTs), cohort studies, and case series using PubMed, CINAHL, and Medline to identify relevant articles through 1 May 2021. Twenty-six applicable studies were found in which 11 compared tele-rehabilitation to conventional clinic-based PR; 11 evaluated tele-rehabilitation using the patient’s baseline status as control; and four compared tele-rehabilitation to no rehabilitation. Despite the different technologies used across studies, tele-rehabilitation was found to be both a feasible and an efficacious option for select patients with lung disease. Outcomes across these studies demonstrated similar benefits to traditional PR programs. Thus the existing data does not show that remotely based PR waters down the effectiveness of conventional PR. Use of remotely based PR is a feasible and effective option to deliver PR, especially for patients with significant barriers to conventional clinic-based PR. Additional, well-conducted RCTs are needed to answer the questions regarding its efficacy, safety, cost-effectiveness and who, among patients with COPD and other lung diseases, will derive the maximum benefit.